Is care based on comprehensive geriatric assessment with mobile teams better than usual care? A study protocol of a randomised controlled trial (The GerMoT study). Issue 10 (10th October 2018) - Ekdahl, Anne Wissendorff; Axmon, Anna; Sandberg, Magnus; Steen Carlsson, Katarina
Abstract : Introduction: Comprehensive geriatric assessment (CGA) is a multidimensional, interdisciplinary diagnostic process used to determine the medical, psychological and functional capabilities of frail older people. The primary aim of our current study is to confirm whether CGA-based outpatient care is superior than usual care in terms of health-related outcomes, resource use and costs. Methods and analysis: The Geriatric Mobile Team trial is designed as a single-centre randomised, controlled, assessor-blinded (at baseline) trial. All participants will be identified via local healthcare registries with the following inclusion criteria: age ≥75 years, ≥3 different diagnoses and ≥3 visits to the emergency care unit (with or without admittance to hospital) during the past 18 months. Nursing home residency will be an exclusion criterion. Baseline assessments will be done before the 1:1 randomisation. Participants in the intervention group will, after an initial CGA, have access to care given by a geriatric team in addition to usual care. The control group receives usual care only. The primary outcome is the total number of inpatient days during the follow-up period. Assessments of the outcomes: mortality, quality of life, health care use, physical functional level, frailty, dependence and cognition will be performed 12 and 24 months after inclusion. Both descriptive and analytical statistics will be used, in order to compare groups and for analyses of outcomes over time including changes therein. The primary outcome will be analysed using analysis of variance, including in-transformed values if needed to achieve normal distribution of the residuals. Ethics and dissemination: Ethical approval has been obtained and the results will be disseminated in national and international journals and to health care leaders and stakeholders. Protocol amendments will be published in ClinicalTrials.gov as amendments to the initial registration NCT02923843 . In case of success, the study will promote the implementation of CGA in outpatient care settings and thereby contribute to an improved care of older people with multimorbidity through dissemination of the results through scientific articles, information to politicians and to the public. Trial registration number: NCT02923843 ; Pre-results.